Breaking the ice: Supporting collaboration and the development of community online - Julie Dixon; Heather Crooks; Karen Henry (The Canadian Network for Innovation in Education (CNIE), 2006)
This study explores the concept of transactional distance, a term coined by Moore (1993), which relates to the distance that exists in all learning relationships and can be more evident and potentially problematic in online learning environments. Reducing this psychologically perceived distance to help learners develop social presence in support of collaborative relationships and the development of community in online learning environments is the purpose of this research. Icebreakers are fun activities that help people get to know each other. These activities can potentially ameliorate the perceived distance in online learning environments. Two author-developed icebreakers were used in a preliminary study involving university undergraduates and instructors in online environments. Respondents took part in an icebreaker at the start of a semester and at the mid-point after which they completed a questionnaire about perceived value of icebreakers. Early results were positive and have led to recommendations for practice.